Recovery kinetics following small-sided games in competitive soccer players: does player density size matter? - Papanikolaou, K.; Tsimeas, P.; Anagnostou, A.; Varypatis, A.; Mourikis, C.; Tzatzakis, T.; Draganidis, D.; Batsilas, D.; Mersinias, T.; Loules, G.; Poulios, A.; Deli, C. K.; et al. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To examine the recovery kinetics of exercise-induced muscle damage (EIMD), neuromuscular fatigue, and performance following small-sided games (SSGs) of different densities in soccer.